Isavuconazole Kinetic Exploration for Clinical Practice - Léa Darnaud; Fabien Lamoureux; Cendrine Godet; Sandrine Pontier; Alexia Debard; Nicolas Venisse; Pauline Martins; Didier Concordet; Peggy Gandia (Adis, Springer Healthcare, 2018)
Abstract Background Isavuconazole is a new antifungal prodrug for the treatment of invasive aspergillosis and mucormycosis. As no clear pharmacokinetic-pharmacodynamic relationship has been established for patients, therapeutic drug monitoring is not currently required. However, as isavuconazole is a new drug, clinicians are sometimes sceptical about the exposure achieved in their patients and seek pharmacokinetic exploration. A minimal response consists of determining that the patient's pharmacokinetic profile agrees with profiles reported by Desai et al. using concentrations from the SECURE study. Methods Based on one concentration and Desai et al.'s population-pharmacokinetic model, it is possible to estimate a patient's most likely pharmacokinetic profile. If a patient's pharmacokinetic profile is close to the profiles reported by Desai et al., therapeutic drug monitoring is not required. In contrast, when the pharmacokinetic profile differs from the Desai et al. profiles, isavuconazole concentration monitoring and pharmacokinetic profile modeling are the only methods for obtaining information on a patient's exposure and the efficacy of isavuconazole. Results Four patients presented with surprising pharmacokinetic profiles, unexplained by drug interactions or cytochrome P450 3A4/5 polymorphisms. For two of them, a drug dosage adjustment was proposed and applied by clinicians, together with a check for a new pharmacokinetic profile a few days later. Conclusions Collecting one blood sample just before the first maintenance dose to make an early estimation of the patient's most likely pharmacokinetic profile is one method of identifying patients with outlier pharmacokinetic behavior.